A long history of cloud and forest migration from Lake Consuelo, Peru - Urrego, D. H.; Bush, M. B.; Silman, M. R. (Quaternary Research, 2010)
The complete paleoecological history from Lake Consuelo forest yields a record of ground-level cloud formation and changes in its lower altitudinal limit over the last 46,300 cal yr BP. The timing of early lake level fluctuations prior to 37,000 cal yr BP appears sensitive to North Atlantic temperature oscillations, corresponding to Dansgaard-Oeschger interstadials 11, 10 and 8 recorded in GISP2. After the LGM, the first hint of warming is recorded in Lake Consuelo at 22,000 call yr BP and agrees with other estimates for the region. The mid-Holocene (7400-5000 cal yr BP) was the period of highest rates of change and most significant reorganizations in the Consuelo forest. These community changes resulted from a regionally widespread dry period. Results from Lake Consuelo indicate that moisture availability, mediated through cloud cover, played the most significant role in ecological change in this system. Rates of past climate fluctuations never exceeded the forest capacity to accommodate change. Unfortunately, this might not be the case under predicted scenarios for the end of the current century. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 1903; 564VS Times Cited:8 Cited References Count:85Y